2008
DOI: 10.1080/09297040802291715
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with Autism can Categorize Facial Expressions

Abstract: The ability of high-functioning individuals with autism to perceive facial expressions categorically was studied using eight facial expression continua created via morphing software. Participants completed a delayed matching task and an identification task. Like undergraduate male participants (N = 12), performance on the identification task for participants with autism (N = 15) was predicted by performance on the delayed matching task for the angry-afraid, happy-sad, and happy-surprised continua. This result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…When task demands are taken into account, the evidence does not support a general FER accuracy deficit in high-functioning adolescents and adults with ASD. Although some studies do show such a deficit (Dalton et al 2005;Macdonald et al 1989;Tantam et al 1989) others do not (Baron-Cohen et al 1997;Capps et al 1992;Homer and Rutherford 2008), at least when analysis is limited to the six basic emotions. Highfunctioning individuals do appear to have more difficulty recognizing complex emotions, such as guilt, shame, and envy (e.g., Baron-Cohen et al 1997).…”
Section: Task Demandsmentioning
confidence: 93%
See 1 more Smart Citation
“…When task demands are taken into account, the evidence does not support a general FER accuracy deficit in high-functioning adolescents and adults with ASD. Although some studies do show such a deficit (Dalton et al 2005;Macdonald et al 1989;Tantam et al 1989) others do not (Baron-Cohen et al 1997;Capps et al 1992;Homer and Rutherford 2008), at least when analysis is limited to the six basic emotions. Highfunctioning individuals do appear to have more difficulty recognizing complex emotions, such as guilt, shame, and envy (e.g., Baron-Cohen et al 1997).…”
Section: Task Demandsmentioning
confidence: 93%
“…Both Homer and Rutherford (2008) and Teunisse and de Gelder (2001) used mixed facial expressions to examine categorical perception differences between high-functioning adults with ASD and controls, and the former study found no abnormalities in ASD, while the latter study did. However, Homer and Rutherford (2008) found increased reaction times in the ASD group (Teunisse and de Gelder did not report whether there were group differences in reaction times). Another study using blended expressions (Castelli 2005) found no differences between children with ASD at various levels of functioning (mental age ranged from 6-14) and TD controls; however, group matching in this study was not very precise.…”
Section: Task Demandsmentioning
confidence: 95%
“…For example, Homer and Rutherford (2004) found that individuals with ASD do process faces holistically, at least under some circumstances. When the authors used a delayed matching task with relatively short presentation times of the face stimuli (750 ms) that would encourage holistic processing (Celani, Battacchi, & Arcidiacono, 1999;Hole, 1994), they found that individuals with ASD perceived emotional expressions categorically as did their age-, gender-, and IQ-matched control group.…”
mentioning
confidence: 97%
“…In another study using emotion blends, Teunisse and de Gelder (2001) found atypical responses to anger-sadness and anger-fear blends but intact responses to happy-sad blends among individuals with ASD. In contrast, Homer and Rutherford (2008) used numerous emotion blends and documented primarily intact performance among individuals with ASD. Only one study has examined FER perceptual sensitivity based on fine grain progressions from neutral to full expression (using the emotional multimorph task) among individuals with ASD.…”
mentioning
confidence: 99%